Research on the humanistic spirit and contemporary value of Tai Chi from the perspective of intangible Cultural Heritage - SUN, Mingyi (The Journal of the International Society of Chinese Health Practices, 2024)
Research purpose: in May 2006, Tai Chi included in the first batch of national intangible cultural heritage list, in December 2020, the United Nations educational, scientific and cultural organization also officially announced the Tai Chi included in the global human intangible cultural heritage representative list, the popularization and promotion of Tai Chi in the world, undoubtedly has an important role. In the "Healthy China 2030" planning outline also pointed out: " we should vigorously promote dragon and lion dance, Tai Chi, fitness Qigong, soft ball and other traditional ethnic sports."Therefore, we must follow the national policy of the development of The Times, take the improvement of the better life of the people as the center, face up to the function of Tai Chi, and effectively serve the people, for the benefit of the people. Tai Chi has greatly enhanced the attraction of China's intangible cultural heritage in the world, and become the expression of the Chinese nation to establish the image of a great country and build the soft power of a great country. Under the intangible cultural heritage horizon and under the background of economic globalization, cultural diversity, as an important part of Chinese martial arts Tai Chi has an obligation to assume the burden of inheriting Chinese excellent traditional culture, to explore the humanistic spirit and contemporary value is not only the era demand, but also the important path of power traditional martial arts culture revival. From the perspective of "intangible cultural heritage", this paper explores the humanistic spirit and contemporary value of Tai Chi, and aims to build a sustainable development model for the contemporary inheritance of Tai Chi. Research methods: this study mainly uses the literature analysis, logic analysis, case analysis method, involving a large number of Chinese intangible cultural heritage, Tai Chi development papers in the field of research, sorting, induction, to study under the "intangible" vision of Tai Chi humanistic spirit and contemporary significance. Research results: Tai Chi has a unique form of movement and rich historical and cultural heritage. In the process of movement, Tai Chi can not only improve the sensitivity and coordination of the body, so as to exercise a strong body and enhance the comprehensive quality of the human body, but also play a positive role in strengthening the body and mind, so that the practitioners can stimulate their thoughts and enthusiasm through self. Further cultivate their own ideological and moral cultivation, and inherit the Chinese nation's spirit of self-improvement and moral commitment. In the teaching of Tai Chi, apart from the explanation of the most basic sets and exercises, it is necessary to cultivate the concept of martial virtues, martial rites, lifelong sports, and the edification of the humanistic connotation of the Chinese nation. The contemporary value of Tai Chi is mainly as follows: (1) "treating disease" : Tai Chi culture plays an irreplaceable role in advocating national fitness and building a healthy China. In the 21st century, with the continuous decline of national physical fitness, the strategy of "healthy China" came into being, the national fitness movement is gradually popularized, and people pay more and more attention to the cultural promotion of traditional national sports. As an outstanding representative of traditional national sports, Tai Chi is suitable for all ages and has the effect of enhancing physical fitness and preventing diseases. It is a good medicine to cure the diseases of modern social civilization. Existing studies have confirmed that Tai Chi's unique movement pattern and deep and slow breathing state play a role in rehabilitation and improvement of organ system functions in a variety of chronic diseases, and have a certain auxiliary effect. (2) Cultural confidence: Chinese traditional Tai Chi, as the lifeblood of the Chinese nation's "martial spirit" and the cultural cornerstone of the modernization of "sports power", contains extensive and profound historical and philosophical thinking. After summarizing and combing this traditional Chinese culture, practitioners will have a better understanding of the unique historical thoughts of Chinese martial arts, so as to face China's traditional sports civilization more squarely. It has taken on the historical consciousness and modern responsibility of inheriting and carrying forward the excellent traditional Chinese culture, and further strengthened its cultural self-confidence. At the same time, the historical heritage culture of Chinese Tai Chi provides a steady stream of spiritual nutrients for practitioners, and the humanistic and confident elements contained here also symbolize the soft power of the excellent traditional Chinese culture in a certain sense, which not only reflects the unique features of the Chinese nation, but also the external expression of the development and growth of the traditional culture of the Chinese nation. In exchange with the world's advanced civilization and art, it reflects the image of a big country and rich cultural and historical deposits. (3) Psychological adjustment: People in modern society are easy to be impatient and emotional impulse, and this kind of anxiety and anxiety is derived from the deep psychology of accelerating the pace of life and increasing the burden on the shoulder. Practicing Tai Chi can provide an opportunity for human beings to communicate and learn from each other, and can also promote human emotional communication, thus reducing social distance and eliminating loneliness in human heart. In addition, Tai Chi follows the basic principle of "integration of body and mind", which not only stresses the physical and mental shape of continuous, soft but not loose, but also needs a calm mind during exercise; Its focus on the mind of undesire, contentment and happiness, help to eliminate the pain in the heart, to achieve physical and mental balance; Tai Chi also pays attention to the spiritual quality of not being harmed by clear reasoning, and not being worried about emotions and emotions, and has the effect of adjusting mental balance and psychological adjustment.Conclusion and Suggestions: Tai Chi, as a boxing type with rich national characteristics in Chinese martial arts, is deeply loved by the Chinese people at home and abroad. It breeds rich humanistic spirit values, and has a strong driving force for the revitalization and development of Chinese society. Under the perspective of "intangible cultural heritage", Tai Chi has attracted wide attention around the world. Tai Chi should explore and innovate on the basis of inheritance and keep pace with The Times. We should be Tai Chi by culture of "harmonious nature", "holy outside king", "the unity of man and nature" philosophy, gradually rise to the way between people, countries, so that more seriously shoulder the protection and spread of Tai Chi culture, to re-examine the contemporary connotation of Tai Chi, thus the continuation of the Chinese fine traditional culture, realize the great rejuvenation of the Chinese nation.